Analyzing Emotional Control in University Athletes: A Cross-Cultural and Gender Perspective - Ahmed Jabbar Abiyra; Sandeep Tiwari; Sandhya Tiwari; Mir Ahsan Ul Haq (Physical Education Theory and Methodology)
Background. Emotional control plays a crucial role in athletic performance and is influenced by factors such as gender and cultural context. Understanding the interplay between emotional regulation and athletic success can provide valuable insights for optimizing performance strategies.